Decentralization, spending quality, and regional development performance: Evidence from West Nusa Tenggara, Indonesia - Hidayat, Rahmad; Khusaini, Mohamad; Kaluge, David; Bintoro, Nugroho Suryo (Universitas Muhammadiyah Yogyakarta, 2026)
This study examines the relationship between fiscal decentralization, public spending quality, and regional development performance in West Nusa Tenggara Province, Indonesia, from 2013 to 2022. This study primarily employs fixed-effects panel regression, supplemented by Structural Equation Modeling (SEM) for mediation analysis, to examine whether fiscal decentralization enhances spending quality and, in turn, improves development outcomes. The results reveal that fiscal decentralization exerts a negative and significant impact on regional development performance, while spending quality shows no significant effect. Moreover, spending quality fails to mediate the relationship between decentralization and development outcomes. Diagnostic and robustness tests support the consistency of the estimated results. The findings suggest that fiscal decentralization may contribute to governance inefficiencies and weakened accountability at the local level, rather than improving development outcomes. Therefore, strengthening institutional capacity, accountability mechanisms, and performance-based budgeting is essential for improving local governance performance.